Carbon/H-ZSM-5 composites as supports for bi-functional Fischer–Tropsch synthesis catalysts. Issue 8 (26th January 2016) - Valero-Romero, M. J.; Sartipi, S.; Sun, X.; Rodríguez-Mirasol, J.; Cordero, T.; Kapteijn, F.; Gascon, J.
Abstract : Deposition of pyrolytic carbon on the surface of mesoHZSM-5 improves the activity, C5–C9 selectivity and decreases CH4 selectivity by weakening cobalt-support interaction. Abstract : Mesoporous H-ZSM-5–carbon composites, prepared via tetrapropylammonium hydroxide (TPAOH) post treatment of H-ZSM-5 followed by deposition of pyrolytic carbon, have been used as the support for the preparation of Co-based Fischer–Tropsch catalysts. The resulting catalysts display an improved performance during Fischer–Tropsch synthesis (FTS), with higher activity, higher selectivity towards C5–C9 (gasoline range) hydrocarbons and lower selectivity towards C1 (and C2) than Co/mesoH-ZSM5 (without pyrolytic carbon). This is due to the weaker metal–support interaction caused by the deposited carbon (as revealed by XPS) leading to a higher reducibility of the Co species. Further, the partial deactivation of the Brønsted acid sites by pyrolytic carbon deposition, as was observed by NH3 -TPD, allows the modification of the zeolite acidity. Both the olefin to paraffin (O/P) and the isoparaffin to normal paraffin (I/N) ratios decrease with the increase in the carbon content, opening the door to further tune the catalytic performance in multifunctional FTS operations.